2020
DOI: 10.1039/d0nj04058d
|View full text |Cite
|
Sign up to set email alerts
|

Dual-emissive dye@MOF composite for ratiometric detection and discrimination of two isomers of tetrachlorobenzenediol

Abstract: A dye@MOF composite was screened out for the ratiometric fluorescent detection and discrimination of the two isomers of tetrachlorobenzenediol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…18,19 More significantly, the combination of MOFs with molecular dyes creates an intriguing platform for investigating host-guest energy transfer difficulties. 20,21 In this study, the methyl blue molecules were encapsulated into CUST-580. As expected, the methyl blue@CUST-580 composites exhibited dual emission properties due to the energy transfer from Cd-MOF to the dye molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 More significantly, the combination of MOFs with molecular dyes creates an intriguing platform for investigating host-guest energy transfer difficulties. 20,21 In this study, the methyl blue molecules were encapsulated into CUST-580. As expected, the methyl blue@CUST-580 composites exhibited dual emission properties due to the energy transfer from Cd-MOF to the dye molecule.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 More significantly, the combination of MOFs with molecular dyes creates an intriguing platform for investigating host-guest energy transfer difficulties. 20,21…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al reported a novel chemical sensor based on a fluorescent metal–organic framework for the selective distinction between and analysis of o-xylene and xylene isomers . Du et al utilized a dye@MOF composite that could discriminate between and ratiometrically detect tetrachlorobenzenediol isomers . Yang et al constructed a fluorescent sensor based on gold nanoclusters for the facile differentiation between nitrophenol isomers .…”
Section: Introductionmentioning
confidence: 99%
“…14 Du et al utilized a dye@MOF composite that could discriminate between and ratiometrically detect tetrachlorobenzenediol isomers. 15 nanoclusters for the facile differentiation between nitrophenol isomers. 16 Zhang and co-workers fabricated a carbon dotdecorated chiral porous organic cage hybrid fluorescent sensor for the rapid differentiation between nitrophenol isomers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation